Pathological Diagnosis of Pulmonary Aspergillosis - Jensen, Henrik E.; Becker, Cecilie B. (Seminars in Respiratory and Critical Care Medicine, 2024)
Pulmonary aspergillosis constitutes an increasingly prevalent and potentially fatal complex of mycotic diseases, caused by different species of Aspergillus. The broad spectrum of pathological manifestations associated with pulmonary aspergillosis necessitates a differentiation of commensalism from saprophytic colonization, hypersensitivity reactions, and true invasive infections, which highlights the importance of histopathology as a gold standard in a diagnostic setting. For the past decades, changes in terminology and contradicting contributions from different diagnostic disciplines have made the classification of pulmonary aspergillosis rather confusing. This review offers a categorization of aspergillosis lesions based on what can be histopathologically identified and distinguished, differentiating between acute invasive infection and forms of subacute, chronic, and allergic diseases and coinfections, and summarizes important manifestations of lesions associated with the different forms of pulmonary aspergillosis.
Keywords: pulmonary aspergillosis; histopathology; fungal histology; Aspergillus spp.